A Study on the Quality Criteria of Some Mandarin Varieties and Their Suitability for Juice Processing. (26th August 2014) - Ağçam, Erdal; Akyıldız, Asiye
Abstract : In this study, some composition properties of juices of different mandarin varieties (Robinson (R), Fremont (F), and Satsuma (S)) were determined before and after pasteurisation. L *, a *, b *, and C * values of all varieties were increased after the pasteurisation process. Degradation of ascorbic acid was calculated as 2.20, 16.86, and 24.31% for R, F, and S samples, respectively, after pasteurisation. The highest total carotenoid and phenolic contents were determined in S samples. In general, after the pasteurisation treatment, the total carotenoid content of juices was increased slightly, but total phenolic contents were dramatically decreased. The antioxidant activity of pasteurised samples was increased by approximately 6%. The most abundant carotenoid and flavanone glycoside compound was shown to be β -cryptoxanthin and hesperidin, respectively, in all samples. The most popular fresh and pasteurised juice samples were made from the Robinson variety of mandarin with regard to taste, smell, and general impression.